Review of Five-Level Front-End Converters for Renewable-Energy Applications - Monteiro, Vitor; Tashakor, Nima; Sousa, Tiago J. C.; Kacetl, Tomas; Götz, Stefan; Afonso, Joao L. (Frontiers in Energy Research, 2020)
With the objective of minimizing environment and energy issues, distributed renewable energy sources have reached remarkable advancements along the last decades, with special emphasis on wind and solar photovoltaic installations, which are deemed as the future of power generation in modern power systems. The integration of renewable energy sources into the power system requires the use of advanced power electronics converters, representing a challenge within the paradigm of smart grids. Therefore, this paper presents a review of front-end converters for renewable energy source applications. Since the objective of this paper is not to cover all types of converters, the focus is on single-phase and three-phase multilevel converters (limited to five voltage levels) with a voltage-source structure and with current or voltage feedback control. The review is performed considering the following classifications: (a) Number of active components; (b) Fault tolerance; (c) Control complexity; (d) Requirements of specific capacitor or inductors; (e) Number of independent or split dc-link voltages. Throughout the paper, several topologies are presented and comparisons are made between them, highlighting the pros and cons of each one of them as a candidate for the interface of renewable energy sources with the power grid.